2011
DOI: 10.5251/abjna.2011.2.6.952.963
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical changes during growth and development of ‘Galia’ cantaloupes. II. Chemical changes

Abstract: Chemical changes during growth and development of fruits of three 'Galia' melon cultivars were evaluated. The respiration curves of the three cultivars exhibited a typical climacteric pattern, with peak of respiration coinciding with full maturity (44 DAA) and then decreased. Fruit flesh firmness slightly decreased up to the mature-green stage and then sharply declined during the ripening phase (44-48 DAA). Rind color, total soluble solids (TSS) and total sugars progressively increased during growth and develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
(24 reference statements)
1
3
0
Order By: Relevance
“…The linear response on SSC due to the increasing dose of goat manure incorporated into the growing media was also revealed from the previous research [7]. Another experiment carried out by [16] explained that total soluble solid increased as melon fruit developed and the maximum at 48 days after anthesis of flowers, while the total sugar reached the highest at 44 days after anthesis. At the maximum level of fruit maturity usually, it is characterized visually by full slip at the basal peduncle and the strong aroma of the fruit.…”
Section: A Effects Of Doses Of Goat Manuresupporting
confidence: 56%
“…The linear response on SSC due to the increasing dose of goat manure incorporated into the growing media was also revealed from the previous research [7]. Another experiment carried out by [16] explained that total soluble solid increased as melon fruit developed and the maximum at 48 days after anthesis of flowers, while the total sugar reached the highest at 44 days after anthesis. At the maximum level of fruit maturity usually, it is characterized visually by full slip at the basal peduncle and the strong aroma of the fruit.…”
Section: A Effects Of Doses Of Goat Manuresupporting
confidence: 56%
“…3a-b). Similarly, progressive decrease in phenolics compounds throughout growth and development of fruit was reported in cantaloupe (Abu-Goukh et al, 2011), guava (Bashir and Abu-Goukh, 2003), papaya (Abu-Goukh et al, 2010), maoluang (Butkhup and Samappito, 2011), and pomegranate (Fawolea et al, 2013), however, the observations in present study are in partial agreement with the findings of Ding et al (2001) Decrease in flavonoids content was also reported in pomegranate (1480-220 mg/100 ml juice) by Fawolea et al (2013), in guava (from 28.82-46.08 mg/100 g to 18.65-31.1 mg/100 g DW) by Gull et al (2012) and in strawberry fruit from un-ripe stage (795 mg kg −1 ) to ripe stage (576 mg kg −1 ) by Shin et al (2008). Ilahy et al (2011) reported that during ripening process the flavonoids content increased in tomato cultivars during green to red-ripe stage from 14.1% (Lyco 2) to 27.9% (HYL 13) but their change during orange red to red ripe was negative (in Lyco 2) or remained almost unchanged (in Rio Grande).…”
Section: Changes In Phytochemicalsmentioning
confidence: 89%
“…Rowan et al [38] observed an increase in the proteins content of the melon fruit during maturation. Changes in the proteins content during the fruit development would be linked to various metabolic activities that occur during the plant growth [39,40].…”
Section: Free Amino Acid Crude Proteins and Total Lipids Contentmentioning
confidence: 99%